1995
DOI: 10.1084/jem.181.6.2017
|View full text |Cite
|
Sign up to set email alerts
|

T cell determinants from autoantibodies to DNA can upregulate autoimmunity in murine systemic lupus erythematosus.

Abstract: Summary(NZB x NZW) F1 (BWF1) mice develop spontaneous T cell autoimmunity to VH region determinants of syngeneic anti-DNA before the onset of clinical disease. In this study, we characterized the immunogenicity, MHC binding, and lymphokine secretion patterns induced by T cell determinants from the VH region of one such anti-DNA mAb (A6.1) and examined their role in the regulation of autoimmunity. Determinants were identified by proliferation of syngeneic splenic T cells from young, unprimed BWF1 mice in respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
130
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(133 citation statements)
references
References 40 publications
3
130
0
Order By: Relevance
“…Briefly, spleen cells were cultured with or without peptides for 5 days; supernatants were tested for IgG anti-dsDNA Ab, as described previously (3,4). Briefly, 96-well plates (Costar) were coated with dsDNA (100 g/ml; Sigma-Aldrich) overnight at 4°C.…”
Section: Determination Of T Cell Help For Anti-dna Ab Synthesis By Elmentioning
confidence: 99%
See 2 more Smart Citations
“…Briefly, spleen cells were cultured with or without peptides for 5 days; supernatants were tested for IgG anti-dsDNA Ab, as described previously (3,4). Briefly, 96-well plates (Costar) were coated with dsDNA (100 g/ml; Sigma-Aldrich) overnight at 4°C.…”
Section: Determination Of T Cell Help For Anti-dna Ab Synthesis By Elmentioning
confidence: 99%
“…Proteinuria and blood urea nitrogen were tested using Albustix and Azostix (range, 0 -4ϩ), respectively, and creatinine was estimated by reagents from Stanbio Laboratories (San Antonio, TX), as described previously (4,20).…”
Section: Assessment Of Clinical Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Following repeated immunization, even these engineered antibodies do trigger an apparently allotypic response. We have recently utilized the novel technology of naked DNA vaccination [53][54][55][56][57][58][59][60][61][62] to generate self-specific protective immunity against C-C chemokines and inhibit EAE. 63 Resistance could be transferred by C-C chemokine-specific neutralizing antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Theories explaining the polyreactivity that is typical of the human disease include cross-reactivity of antiforeign and anti-self Abs (24), somatic mutation of the anti-foreign response to generate autoreactivity (25,26), and epitope spreading of the immune response to target self Ags (27)(28)(29)(30)(31)(32)(33). We have previously shown that cross-reactivity of the serum Abs accounts for much of the anti-self response in these mice (18).…”
Section: Dweysvwlsn-map-specific T Cells Are Not Cross-reactive With mentioning
confidence: 99%